Alteration of biomechanical properties of burned skin. Issue 4 (June 2015) - Held, M.; Rahmanian-Schwarz, A.; Rothenberger, J.; Schiefer, J.; Janghorban Esfahani, B.; Schaller, H.E.; Jaminet, P.
Abstract Background The prevalence of burns in the general population is high. Despite new research findings, skin burns and its resulting tissue damage are still not entirely understood. In particular, little is known about the depth-dependent alteration of skin biomechanical properties of these wounds. Methods Thirty-six burn wounds with six different depths were generated on the abdomen of six Göttingen minipigs. The alteration of skin biomechanical properties was evaluated objectively after 15 and 360 min using a Cutometer device. Biopsies for histological evaluation were taken and the depth of burn was correlated with biomechanical properties. Results Firmness of skin (R0), overall elasticity (R8) and calculated elasticity (Ue) demonstrated a continuous decrease with an increasing depth of burn 15 min after wound generation. Gross elasticity (R2), net elasticity (R5) and amount of elasticity of the whole curve (R7), however, showed an increase of values with increasing depth of injury. A further decrease of elasticity was demonstrated 360 min after wound generation. Conclusion The alteration of skin biomechanical properties is a function of damaged tissue structures. The presented results demonstrate a depth-dependent decrease of principal elastic parameters with an increasing depth of burn and the results indicate progressive tissue damage over the time.